1998
DOI: 10.1177/108705719800300406
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Screening Assay for the Phosphorylation of Mitogen-Activated Protein Kinase in Cells

Abstract: Mitogen-activated protein (MAP) kinases are serine/threonine kinases that are activated by phosphorylation and are involved in the cellular response to various physiologic stimuli and stress conditions. Because MAP kinases play an important role in cellular functioning, a screening assay to determine the phosphorylation of MAP kinase upon various conditions was desirable. Therefore, we have developed a cellular enzyme-linked immunosorbent assay (Cell-ELISA), in which the phosphorylated forms of p42MAPK and p44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Also the oxidative stressinduced phosphorylation and activation of the Ser/Thr kinase Raf-1, a downstream effector molecule of p21 ras , has been described in several cell types as well (Kasid et al, 1996;Abe et al, 1998). Other studies have established that oxidative stress induces the phosphorylation and activation of MAPKs (Guyton et al, 1996;Lander et al, 1996;Peus et al, 1999a;Dérijard et al, 1994;Stevenson et al, 1994;Zhang et al, 2000;De Wit et al, 1998;Bapat et al, 2001).…”
Section: Ros and Phosphorylation/dephosphorylation Pathwaysmentioning
confidence: 94%
See 1 more Smart Citation
“…Also the oxidative stressinduced phosphorylation and activation of the Ser/Thr kinase Raf-1, a downstream effector molecule of p21 ras , has been described in several cell types as well (Kasid et al, 1996;Abe et al, 1998). Other studies have established that oxidative stress induces the phosphorylation and activation of MAPKs (Guyton et al, 1996;Lander et al, 1996;Peus et al, 1999a;Dérijard et al, 1994;Stevenson et al, 1994;Zhang et al, 2000;De Wit et al, 1998;Bapat et al, 2001).…”
Section: Ros and Phosphorylation/dephosphorylation Pathwaysmentioning
confidence: 94%
“…Various studies have established that oxygen free radicals can cause the phosphorylation and activation of numerous signaling proteins (Finkel and Holbrook, 2000), including Receptor Tyrosine Kinases (RTK) (Gamou and Shimizu, 1995;González-Rubio et al, 1996), PKC (Gopalakrishna and Jaken, 2000), PLCg1 (Schieven et al, 1993), Src kinases (Aikawa et al, 1997;Hardwick and Sefton, 1997), MAPKs (Dérijard et al, 1994;Stevenson et al, 1994;De Wit et al, 1998;Bapat et al, 2001), protein kinase B , and transcription factors (Devary et al, 1991;Meyer et al, 1993). As an example the effects on the RTK and MAPK pathway will be discussed.…”
Section: Ros and Phosphorylation/dephosphorylation Pathwaysmentioning
confidence: 98%
“…There is increasing evidence suggesting that reactive oxygen species activate or inactivate signaling pathways involving tyrosine and serine/threonine kinases and thereby, regulate phosphorylation of MAPKs. Indeed, MAPKs are reported to be activated in response to various forms of oxidative stress such as UV irradiation [1], hydrogen peroxide [2], nitric oxide [3], and peroxynitrite (ONOO − ) [4–7]. Of particular interest is the highly reactive ONOO − , which is involved in oxidative damage detected in several pathological conditions such as inflammation, ischemia/reperfusion injury, atherosclerosis and neurological disorders (reviewed in [8,9]).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, the involvement of oxygen free radicals in intrinsic signal transduction pathways leading to cell division has been studied in great detail. It has been demonstrated that extracellular addition of inducers of oxidative stress, such as hydrogen peroxide (H 2 O 2 ), can induce the phosphorylation and activation of several proteins that are involved in these signaling pathways (6)(7)(8)(9)(10)(11)(12)(13). Moreover, recent studies revealed that H 2 O 2 is produced upon stimulation of cells with epidermal growth factor (EGF) (14) or platelet-derived growth factor (PDGF) (15,16).…”
mentioning
confidence: 99%